Dissipative Hamiltonian realisation and decentralised saturated control of multi‐machine multi‐load power systems. Issue 9 (1st June 2013) - Liu, Yanhong; Li, Jianyong; Ding, Qingqing; Chu, Bing
Abstract : Using the energy‐based Hamiltonian function method, this study investigates the decentralised saturated excitation control of multi‐machine multi‐load power systems based on the structure preserving dynamic model. First, a constructive procedure is proposed for the dissipative Hamiltonian realisation of non‐linear differential algebraic systems and transform the power system to its equivalent dissipative Hamiltonian system. Constant feedforward control is proposed to adjust the system to the desired equilibrium point. Then, we put forward a decentralised saturated excitation controller using only the local information. Simulation results show that the proposed control scheme can effectively improve the transient stability of the power system.